Alleviating effect of IAA on salt stressed Phaseolus mungo (L.) with reference to growth and biochemical characteristics - Guru Devi, R; Pandiyarajan, V; Gurusaravanan, P (Recent Research in Science and Technology, 2012)
Sodium Chloride (i.e., 25mM, 50mM, 100mM and 200mM) induced salinity effect in black gram caused significant reduction in germination, seedling growth, root and shoot length, fresh weight and leaf area. A reduction in protein content, and nitrate reductase activity was observed in all the concentrations of sodium chloride treated plants. However, the proline level, free amino acid, peroxidase and catalase activities were increased with the increase in the concentration of sodium chloride. Foliar application of 15 ppm IAA to the sodium chloride stressed plants caused an alleviating effect on the salt stressed plants and increased crop yield.